3D-printed pulsator to enhance mass transfer in electrochemical reactors - Kavin Teenakul; Luis Fernando Arenas; Jonas Hereijgers (HardwareX)
This study presents a cost-effective diaphragm pulsator, constructed for approximately €500, designed to enhance mass transport in laboratory electrochemical reactors. The pulsator allows accurate control of pulsation frequency between 1 Hz and 6 Hz and displacement volume, with simple programmability using an Arduino microcontroller. The design features multiple chambers that effectively isolate corrosive liquids from the mechanical components, ensuring durability and extended operational life. The pulsator’s 3D-printed components can be customized with different materials to suit various applications. Engineered to generate a pulsating flow profile that closely resembles a sinusoidal wave, video tracking analysis confirmed the sinusoidal nature of the flow, demonstrating consistent flow profile generation with adjustable frequency and amplitude. The maximum volume displacement achieved was 11.9 mL, which was reduced to 2.0 mL when the electrochemical cell was connected. Limiting current experiments with a ferri/ferrocyanide electrolyte showed that the mass transport coefficient of a typical cell increased from 2.3 × 10−3 cm/s under constant flow to 4.5 × 10−3 cm/s under pulsating conditions. These findings validate that the adjustable, Arduino-programmable sinusoidal pulsation generated by the diaphragm pulsator offers a practical and customizable method for enhancing mass transport in small-scale electrochemical reactors.